Development of a Topical Gel Preparation with Joastic Plant (Jatropha curcas L) Leaf Extract and White Turmeric (Curcuma zedoaria) as Anti-Inflammatory - Anggelia, Anggelia; Sulastri, Titin; Suwitono, Marvel Reuben (Jurnal Biologi Tropis, 2025)
The development of a topical gel preparation with (Jatropha curcas L). joastic plant leaf extract and (Curcuma zedoaria) white turmeric aims to produce a product with optimal anti-inflammatory activity. This study involves the formulation of the gel with a combination of extracts from these two plants, which were extracted using ethanol as a solvent. Organoleptic tests for F1, F2, and F3 revealed a deep green gel with the distinctive odor of Jatropha leaves and White Turmeric, and a semi-solid gel. Homogeneity tests showed that F1, F2, and F3 were evenly distributed without any coarse grains. Meanwhile, pH tests for F1 (5), F2 (5.67), and F3 (6.33) met the pH standard for safe use on the skin. Viscosity tests for F1 (8.584cps), F2 (8.604cps), and F3 (8.666cps) indicated a good gel viscosity range. The spreadability test was conducted to measure the gel's ability to spread on the skin surface, while the adhesion test assessed the length of time the gel adhered to the skin with results of F1 5.23cm; F2 5.36cm and F3 5.71cm. The results of the F1 adhesion test were 3 seconds; F2 5 seconds and F3 9.33 seconds. Overall test results showed that the formulated gel had good physical properties, with an appropriate pH, stable viscosity, and satisfactory spreadability and adhesion. These findings suggest that the topical gel containing (Jatropha curcas L) and (Curcuma zedoaria) extracts holds potential as an alternative for topical anti-inflammatory treatment.